Domestic and heroic in Tennyson's poetry - Hair, Donald S. (University of Toronto Press, 1981)
Tennyson shared the assumptions of his age concerning the value of family life, and treated the domestic as the source of the heroic in both action and character. This book provides a critical examination of these major Victorian themes as they appear in Tennyson's poetry and demonstrates how the poet's assumptions illuminate his use of elegy, idyl, and epyllion and his treatment of romance. Professor Hair analyses In Memoriam, the English Idylls, The Princess, and Idyls of the King; he examines Tennyson's view of the family as the model of social order, a civilizing influence on the nation, and a place where the greater man, or hero, is nurtured; and he reveals how much of Tennyson's poetry explores the link between domestic and heroic. He also discusses the patterns into which these pervasive domestic concerns fall, with emphasis on the most significant: separation and reunions. The myth of Demeter and Persephone, the Biblical story of Ruth, and the Sleeping Beauty fairy tale are all versions of Tennyson's treatment of this pattern. The English Idylls and other idyls and epyllia are explored as varying combinations of romance, satire, tragedy, comedy, and irony, with a detailed analysis of The Princess, the most complex of these medleys. Idylls of the King, wherein the fate of Camelot rests on the marriage of Arthur and Guinevere, is treated as the fullest exploration of the link between domestic and heroic.